A sociological analysis of indigenous curricula in Taiwanese universities: Power and identity - Chen, Ming-Kuo; Shih, Yi-Huang (Edelweiss Applied Science and Technology, 2025)
Education serves as a critical instrument for promoting social equity, reducing systemic disparities by creating opportunities for upward mobility and fostering inclusive participation in civic life. Within multicultural contexts such as Taiwan, education also assumes the essential responsibility of sustaining cultural diversity and revitalizing Indigenous knowledge systems. However, the educational experiences of Indigenous peoples have historically been shaped by assimilationist policies that marginalized their languages, cultures, and epistemologies. As Indigenous students transition into higher education, particularly universities, it is vital to examine how their curricular and learning experiences are influenced by underlying power relations and processes of identity construction. Adopting a sociological lens, this article critically investigates these dynamics and reflects on their implications for advancing educational equity and fostering inclusive educational practices. Drawing on the interrelated concepts of power and identity, this article proposes the following strategies for the development of Indigenous curricula in higher education institutions: (1) Curricula should be grounded in Indigenous worldviews and knowledge systems; (2) Indigenous scholars and communities must lead the curriculum development process; (3) The design of curricula should reflect the authentic needs, voices, and lived experiences of Indigenous peoples; (4) Learning experiences that reinforce students’ cultural heritage can support the reconstruction of identity and the development of cultural confidence; (5) Curriculum frameworks must recognize and respect the cultural diversity of Indigenous students and avoid reducing their identities to singular narratives or stereotypical representations.